Community origin and institutionalization of the National University of the Center of Peru - Lázaro-Aquino, Teódulo Gerardo (2022)
The article aims to analyze the trajectory of a university organization from its private-communal origin to its nationalization, as a result of the collective action, organization, participation, mobilization and resources of the peasant communities, union, popular and economic organizations of the mountains. central Peru. That is, the origin and institutionalization of the Communal University of Peru (UCP) to the National University of the Center of Peru (UNCP), which shows important stages such as the creation of the organizing commissions since 1928, the configuration of the foundational bases, the enrollment in public records, the officialization of its operation on December 16, 1959, the opening of academic work and the nationalization on December 20, 1961, which marked its subsequent institutionality. Academically, it promoted the formation of regional human capital; the incorporation and transfer of technology to the communities and their environment; as well as the social, economic and political transformation of the central region, with an environmental institutional commitment.